Predictors of personality development in mid and late adulthood: the role of life satisfaction, cognition and health - an investigation of differentiating effects of aging. Findings from the "Interdisciplinary Longitudinal Study on Adult Development and Aging (ILSE)" - Tauber, Benjamin (2017)
Objective: Identifying the sources of personality development across the adult life span is a key issue of current personality research. The present dissertation investigates the long-term, mutual inter-relationships of personality traits with life satisfaction (publication 1), constructs of health (publication 2) and different cognitive abilities (publication 3). Guiding questions where: (1) Can personality and its development be predicted by these different domains? (2) Are these predictions sensitive to aging, namely the change from middle adulthood to old age? Method: Analyzes were based on data from the “Interdisciplinary Longitudinal Study on Adult Development and Aging (ILSE)”, a prospective German cohort study of mid adulthood (Age baseline = 44y) and old age (Age baseline = 63y), longitudinally spanning across 12 years. Participants were recruited stratified by cohort (N mid adulthood = 502, N old age = 500), sex (♂ = 52%, ♀ = 48%) and region of residence (Region of Heidelberg = 50%, Region of Leipzig = 50%). After 12 years the overall response rate was 76.7%. Personality traits were measured by the 60-item NEO-FFI inventory. Life satisfaction was assessed by a single-item measurement and health variables by an individual’s self-rating and an extensive physician-rating. Cognitive abilities (processing speed, crystalline intelligence, fluid intelligence) were measured by a comprehensive test-battery of various well-established cognitive tests of different cognitive domains (e.g. processing speed was measured by the Digit Symbol Test, a subtest of the WAIS-R). Furthermore, gender, education (years of education) and depression (SDS, self-rated depression scale) were used as control variables. In publication 1 and 2 multi-group cross-lagged panel analyses were used and in publication 3 multi-group dual latent change regression models were conducted. Results: The results of publication 1 suggest that there is only limited evidence of life satisfaction predicting the personality traits extraversion and neuroticism in later life. The path coefficients were small and only significant in the old cohort. Integrating health into the models weakened the inter-relationships. The results of publication 2 show that physician-rated health is an important predictor for the personality traits neuroticism, extraversion (uncontrolled) and agreeableness at later life. Self-rated health demonstrated to be more of an outcome measure of earlier personality in adulthood. There were no considerable cohort differences regarding the cross-lagged predictor paths. The results of publication 3 illustrate the important role of cognitive abilities as a predictor for 12-year personality changes in the personality traits neuroticism, extraversion and openness. Cohort differences, again, were limited. Conclusions: All in all, health (publication 2) and cognitive abilities (publication 3) are demonstrated to be important driving forces for following personality development in adulthood for all of the Big-Five personality traits, except conscientiousness. Physician-rated health was a particularly important predictor for later life neuroticism and agreeableness, while cognitive abilities proved to be important predictors for following personality changes in neuroticism, extraversion and openness. Life satisfaction (publication 1) is demonstrated to be more of an outcome than a predictor of later personality. Moreover, there were (almost) no effects of aging on the cross-relationships, highlighting the non-transient importance of the predictor domains across life span. Lastly, a differential perspective is highly recommended for future research, as the results appeared to depend highly on the personality trait and predictor considered.
Keywords: Hochschulschrift